Influence of communication determinants on safety commitment in a high-risk workplace: a systematic literature review of four communication dimensions - Zara, Jamil; Nordin, Shahrina Md; Isha, Ahmad Shahrul Nizam (Frontiers in Public Health, 2023)
Health, safety, and environment (HSE) are a critical aspect of any industry, particularly in high-risk environments such as the oil and gas industry. The continuous accident reports interpret the requirement for effective implementation of safety rules, regulations, and practices. This systematic literature review examines the relationship between safety communication and safety commitment in high-risk workplaces specifically focusing on the oil and gas industry. The review comprises of 1439 articles from 2004 to 2023, retrieved from Scopus and Web of Science databases following the PRISMA comprehensive guidelines. The study has considered safety communication, communication climate, and communication satisfaction to evaluate their influence on safety commitment under occupational health and safety. The study identifies the safety commitment issues, their underlying factors discussing the measures to prevent and reduce the accident and incidents and highlight the preventive measures for future research. It also signifies the variables influencing the accident and incident rates. The research underscores the importance of communication dimensions and the need for workers to possess adequate skills, knowledge, and attitude regarding occupational safety and health procedures. Moreover, the study contributes to the industrial and academic domains by improving organizational safety commitment, promoting a safety culture, and developing effective communication strategies. Furthermore, the practitioners can benefit from the comprehensive overview to develop, evaluate, and enhance the occupational safety.